Studying abroad while staying at home in Australia: diverse intercultural learning and teaching through partnerships (Comparative & International Education Series, 2021)
As authors at two metropolitan universities in Australia, we contribute to internationalizing the curriculum by including international and intercultural approaches and perspectives into our teaching, offering ‘alternatives to studying abroad’. We are critical of the ‘edutourism’ that may take in a visit to an orphanage, a three-week placement at a school practicing didactic rote learning, and a visit to the Taj Mahal. Our chapter draws on collaborative partnerships with academics, teachers, students and performing artists from different countries using a blended teaching and learning environment and a designated website. Through reflection, anecdotal feedback, questionnaires and interview data, we employ thematic analysis to inform our findings. We discuss two overarching themes (benefits and challenges) in relation to the value of promoting diversity through exploring partnerships. Our alternative to study abroad has provided a more inclusive opportunity to engage in diverse teaching and learning environments which would have otherwise been inaccessible. While there are challenges associated with alternatives to study abroad, we found the experience worthy to be explored and replicated as an effective way to foster equity in study abroad.